2006
DOI: 10.1124/jpet.106.101774
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogen and Anticancer Drug Transport by Mrp2 in Vivo: Studies UsingMrp2(Abcc2) Knockout Mice

Abstract: The ATP-binding-cassette (ABC) transporter multidrug resistance protein (MRP) 2 (ABCC2) forms a natural barrier and efflux system for various (conjugates of) drugs, other xenotoxins, and endogenous compounds. To obtain insight in the pharmacological and physiological functions of Mrp2, we generated Mrp2 knockout mice, which were viable and fertile but suffered from mild hyperbilirubinemia due to impaired excretion of bilirubin monoglucuronides into bile. The mice also had an 80-fold decreased biliary glutathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
159
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(174 citation statements)
references
References 35 publications
11
159
1
2
Order By: Relevance
“…Two distinct naturally occurring sequence variants in the rat Abcc2 gene, either at codon 401 (GY/ TR − ) [133] or at codon 855 (EHBR) [60], lead to premature stop codons and to a lack of the Abcc2 protein from the hepatocyte canalicular membrane [13,114,133]. Recently, Abcc2-knock-out mice have been generated and characterized by several groups [18,121,177]. These Abcc2-deficient mice are apparently healthy and fertile, as are As recommended by the Human Genome Variation Society (http://www.hgvs.org/mutnomen) and by ref [26], nucleotide position +1 is the A of the ATG of the translation initiation codon in the ABCC2 cDNA sequence, "c." describes a nucleotide change in relation to the ABCC2 cDNA sequence, "p." describes a change in relation to the deduced ABCC2 protein sequence, and "X" denotes a premature stop codon b If not indicated otherwise, the diagnosis of Dubin-Johnson syndrome was based on the histopathology of the liver and on elevated serum levels of conjugated bilirubin c PolyPhen online tool for assessing potential effects of amino acid substitutions, http://genetics.bwh.harvard.edu/pph d Single nucleotide polymorphism database, http://www.ncbi.nlm.nih.gov/SNP; data based on NCBI dbSNP build 125, regular updates available e Identified in cell lines derived from Japanese individuals f Probably reduced ABCC2 mRNA levels due to nonsense-mediated mRNA decay [167] the Abcc2-deficient rats.…”
Section: Transcriptional and Posttranscriptional Regulation Of Abcc2mentioning
confidence: 99%
See 1 more Smart Citation
“…Two distinct naturally occurring sequence variants in the rat Abcc2 gene, either at codon 401 (GY/ TR − ) [133] or at codon 855 (EHBR) [60], lead to premature stop codons and to a lack of the Abcc2 protein from the hepatocyte canalicular membrane [13,114,133]. Recently, Abcc2-knock-out mice have been generated and characterized by several groups [18,121,177]. These Abcc2-deficient mice are apparently healthy and fertile, as are As recommended by the Human Genome Variation Society (http://www.hgvs.org/mutnomen) and by ref [26], nucleotide position +1 is the A of the ATG of the translation initiation codon in the ABCC2 cDNA sequence, "c." describes a nucleotide change in relation to the ABCC2 cDNA sequence, "p." describes a change in relation to the deduced ABCC2 protein sequence, and "X" denotes a premature stop codon b If not indicated otherwise, the diagnosis of Dubin-Johnson syndrome was based on the histopathology of the liver and on elevated serum levels of conjugated bilirubin c PolyPhen online tool for assessing potential effects of amino acid substitutions, http://genetics.bwh.harvard.edu/pph d Single nucleotide polymorphism database, http://www.ncbi.nlm.nih.gov/SNP; data based on NCBI dbSNP build 125, regular updates available e Identified in cell lines derived from Japanese individuals f Probably reduced ABCC2 mRNA levels due to nonsense-mediated mRNA decay [167] the Abcc2-deficient rats.…”
Section: Transcriptional and Posttranscriptional Regulation Of Abcc2mentioning
confidence: 99%
“…Today, many sequence variants in the ABCC2 gene have been identified, as described below, but only some of them cause DubinJohnson syndrome. The hereditary deficiency of ABCC2 in humans, or of Abcc2 in the mutant rats mentioned above, and the recently generated Abcc2 knock-out mouse strains [18,121,177] illustrate the key function of this apical efflux pump in the elimination of anionic conjugates from the body. It should be noted, however, that this loss of ABCC2 function is usually well tolerated and compensated by the upregulation of other membrane transporters, particularly of ABCC3 in the basolateral membrane of hepatocytes [30,82,91].…”
Section: Introductionmentioning
confidence: 99%
“…Besides endogenous compounds and a wide range of drugs, the dietary heterocyclic amine carcinogens PhIP (2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine) and IQ (2-amino-3-methylimidazo[4,5-f]quinoline) are also substrates for ABC transporters in vitro and in vivo (Dietrich et al, 2001a,b;van Herwaarden et al, 2003van Herwaarden et al, , 2006Leslie et al, 2005;Vlaming et al, 2006;Enokizono et al, 2008). PhIP is the most abundant heterocyclic amine in fried or cooked meat, chicken, and fish.…”
Section: Introductionmentioning
confidence: 99%
“…Using Bcrp1-or Mrp2-deficient mice and rats, it was previously shown that Bcrp1 and Mrp2 significantly influence the pharmacokinetics of [ 14 C]PhIP in vivo (Dietrich et al, 2001b;van Herwaarden et al, 2003van Herwaarden et al, , 2006Vlaming et al, 2006). However, since in several studies only radioactivity was measured, no differentiation between parent PhIP and its mutagenic metabolites could be made.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation